Jaboticaba (Myrciaria cauliflora) Fruit Extract Suppressed Aberrant Crypt Formation in 1,2-Dimetylhydrazine-Induced Rats - Ardanareswari, Katharina; Lowisia, Webiana; Soedarini, Bernadeta; Liao, Jiunn-Wang; Chung, Yun-Chin (Plant foods for human nutrition (Dordrecht), 2023)
Early intervention can significantly improve the colorectal cancer survival rate. Foods rich in phenolic compounds, such as jaboticaba ( Myrciaria cauliflora ), may prevent tumorigenesis. We investigated the effectivity of jaboticaba whole fruit ethanolic extract (FEX) in suppressing aberrant crypt foci (ACF), the earliest lesion of colorectal cancer (CRC), in 1,2-dimethylhydrazine (DMH)-induced rats and the underlying mechanisms related to the gut microbiota composition and short chain fatty acid (SCFA). This study was approved by the Institutional Animal Care and Use Committee (IACUC) of Providence University (Trial Registration Number 20180419A01, registration date: 22 December 2018). The FEX contains gallic acid and an especially high ellagic acid concentration of 54.41 ± 1.80 and 209.79 ± 2.49 mg/100 g FEX. The highest total ACF number (150.00 ± 43.86) was recorded in the DMH control (D) group. After 56 days of oral FEX treatment, the total ACF number in the low FEX dosage (DL) group was significantly lower compared to the D group ( p < 0.05). The large-sized ACF (> 5 foci), which has a higher probability of progressing to later stage, was significantly decreased in the high FEX dosage (DH) group. The 16s rDNA metagenomic sequencing of the cecal material revealed that the CRC biomarker Lachnoclostridium was significantly suppressed in the DH group ( p < 0.05), whereas some SCFA-producing taxa and the cecal butyrate concentration were significantly elevated in the DL and DH groups ( p < 0.05). This study demonstrated the potential of jaboticaba whole fruit in CRC prevention, especially in the initial stage, by shifting gut microbiota composition and improving cecal butyrate level.